Factors associated with birth preparedness and complication readiness in Southern Ethiopia: a community based cross-sectional study - Eshetu Andarge; Aderajew Nigussie; Mekitie Wondafrash (BMC, 2017)
Abstract Background Birth preparedness and complication readiness (BP/CR) is a strategy to promote use of skilled maternal and neonatal care so that they can get timely skilled care, particularly during child birth. There is minimal evidence on the factors associated with BP/CR among pregnant women in Ethiopia. Hence, this study aimed to assess the factors influencing BP/CR among pregnant women in Southern Ethiopia for the purpose of improving utilization of skilled attendant at birth. Methods A community based cross-sectional study was conducted among 707 pregnant women in Southern Ethiopia in March 2015. Both quantitative and qualitative methods of data collection were used. For the quantitative study, the study subjects were included in the study by employing multi-stage sampling. Data was entered into Epidata version 3.1 and analyzed using IBM SPSS statistics 20. Level of statistical significance was declared at a p- value of <0.05. For the qualitative study, six FGDs were conducted and analyzed based on the thematic areas. Result The prevalence of BP /CR in Arba Minch Zuria Woreda was found to be 30%. The odds of being prepared for birth and its complications was higher among women from high economic class (AOR = 2.29, 95% CI = 1.16, 4.54), with frequency of antenatal care(ANC) > = 4 (AOR = 4.52, 95% CI = 2.26, 9.02), who received advice on BP &CR (AOR = 1.84, 95% CI = 1.13, 3.01),and who were knowledgeable on labor and delivery(LAD) danger signs (AOR = 1.85, 95% CI = 1.01, 3.44). However, it was lower among women with parity of 2 - 4(AOR = .0.51, 95% CI = 0.31, 0.84) and >4 (AOR = 0.51, 95% CI = 0.31, 0.84) than primiparous women. It was also lower among women from food insecure households (AOR = 0.26, 95% CI = 0.16, 0.42) than their counterparts. Lack of awareness on BP/CR, privacy and respect in health institutions were mentioned by the FGD discussants as barriers to women's preparation for birth. Conclusions The study showed that BP/CR is inadequate among pregnant women in the study area. Improving socio-economic and food security status of women, strengthening community-based education on complete attendance of ANC, and conforming to professional ethical standards were recommended.